Concentration-compactness and universal profiles for the non-radial energy critical wave equation. (June 2016) - Duyckaerts, Thomas; Kenig, Carlos; Merle, Frank
Abstract: In this paper, we give an overview of the authors' work on applications of the method of concentration-compactness to global well-posedness, scattering, blow-up and universal profiles for the energy critical wave equation in the non-radial setting. New results and proofs are also given.